Analisis Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai Politeknik Kesehatan Kemenkes Pontianak Jurusan Analis KesehatanAbstract - B11108088, YENDRA SAPUTRA (Jurnal Manajemen Update, 2015)
The purpose of this research is to know and to analyze the influence of  leadership style on the employee performance at health polytechnics department of health analyst pontianak. Research methodology that is used is descriptive research and associative causal by using documentary study, the questionnaire, and an interview as a technique of data collection. Population in this research is all employees at health  polytechnic department of health analyst pontianak that is as many as 35 people . A writer used SPSS 16.0 in examining the validity, reliability, normality, multikolinearitas, heteroskedastisitas, multiple regression and examined simultaneously and partial in determining the result. Based on the results of  f test,  the value is 13.048 and significance at  0.000 <  0.05. Thus, telling, selling, participating, and delegating simultaneously influence on the employee performance. Based on the results of  t  test, delegating style has significance influence on the employee performance. Key words: leadership style and the employee performance